Pemanfaatan Artificial Intelligence (AI) dan Work Innovation bagi Tenaga Kependidikan Universitas Islam Indragiri Systematic Literature Review Menggunakan Metode Prisma - Syafrinadina; Veri, Jhon; Rifa'i, Ahmad; Widyawati (Jurnal Indragiri Penelitian Multidisiplin, 2026)
The development of information and communication technology (ICT) in the era of the Industrial Revolution 4.0 and Society 5.0 has brought significant changes to the governance of higher education, including among educational staff. This study aims to analyze the utilization of Artificial Intelligence (AI) and work innovation in enhancing the work effectiveness of educational staff at Universitas Islam Indragiri (UNISI). The method used is a Systematic Literature Review (SLR) with a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, through a search of scientific articles in the Scopus and Google Scholar databases using the keywords “Artificial Intelligence,” “Work Innovation,” “Education Staff,” and “Higher Education.” From 273 articles identified, 114 met the inclusion criteria and were analyzed using content analysis techniques. The results show that the implementation of AI plays a crucial role in administrative automation, work efficiency, and data-driven decision-making, while work innovation functions as a reinforcing factor that promotes creativity, adaptability, and collaboration among educational staff in responding to digital transformation. The integration between AI and work innovation creates a synergy that enhances operational effectiveness, professionalism, and service transparency within the university environment. This study emphasizes that the success of AI implementation depends on human resource readiness, organizational culture, and institutional policy support, and provides both conceptual and practical contributions for Universitas Islam Indragiri in realizing its transformation toward a smart university.